Strengthening rehabilitation services in Indonesia: A brief situation analysis - Boya Nugraha; Garry Rahardian Setyono; Irma Ruslina Defi; Christoph Gutenbrunner (Medical Journals Sweden, 2018)
People with disability (PWD) in Indonesia are often neglected by society. Improving their life situation towards full participation in society is crucial. As a health strategy, rehabilitation can improve func-tioning, quality of life and participation in society. However, rehabilitation services in Indonesia need improvement. Making a situation analysis of rehabilitation services and their provision in the country is a pre-requisite to taking any action towards improvement. This paper compiles available data related to disability and rehabilitation services in Indonesia, using the Rehabilitation Services Assessment Tool (RSAT) as a framework. Gaps in provision were analysed, resulting in the compilation of a list of generic recommendations to improve rehabilitation services in the country. Indonesia faces many challenges in rehabilitation services, including the health workforce and the provision of services. This situation analysis and list of generic recommendations may be used in further discussions with relevant stakeholders in the country to develop a national strategy to strengthen rehabilitation services.